use of the virtual learning environment and development of digital competencies of students of the faculty of Administrative Sciences, UNMSM - Eche Querevalú , Pedro (2025)
Due to the COVID-19 pandemic, education in the world and our country had to be carried out remotely and virtually. Due to this, students and teachers had to work in their classes with ICTs, promoting digital competence, otherwise it caused problems such as the digital divide. This article is born from the research that investigated the influence of the Use of the Virtual Learning Environment on the development of Basic Digital Competencies in students of the Faculty of Administrative Sciences of the UNMSM, 2021, in the city of Lima, Peru. The study was of a basic type with a quantitative approach, non-experimental, cross-sectional, descriptive correlational causal design, the method used was hypothetical-deductive and correlational in scope, and a sample of 342 students was worked with. Applying two surveys, a Virtual Learning Environment questionnaire with 20 items and a Digital Competencies questionnaire with 30 items. By systematizing the data with the respective statistics, it was shown that both variables present a considerable positive correlation (Spearman's Rho = 0.765), also, the percentage of variability between them is 60.9% with R square = ,609, ANOVA with significance ,000, testing the significant regression model. We affirm that there is a positive and significant relationship with the use of the Virtual Learning Environment in the development of Digital Competence in university students, confirming the importance of greater investment and use in virtual environments, platforms and digital tools has a significant impact on the digital capabilities of students.